Comparative Evaluation Of Surface Roughness After Using Normal Toothbrush Vs Charcoal Toothbrush - Panigrahi, Chandan; R, Vignesh (Journal of Neonatal Surgery, 2025)
Introduction: Charcoal toothbrushes resemble normal toothbrushes in design but incorporate activated charcoal-infused bristles. Charcoal toothbrushes claim to offer additional benefits due to the activated charcoal in their bristles. Charcoal is believed to have adsorptive properties, meaning it can attract and bind certain substances onto its surface. Charcoal toothbrushes are marketed as natural teeth whiteners due to their activated charcoal content. The abrasive nature of charcoal particles may aid in removing superficial stains, providing a potential benefit for individuals seeking a brighter smile. Materials and Methods: permanent and primary tooth samples were subjected to brushing simulation for 10000 cycles (approximately 1 year of brushing) using both normal toothbrush and charcoal toothbrush. Their Pre and Post surface roughness values were evaluated. Results: There was a significant increase in the surface roughness after using the charcoal infused toothbrush. Charcoal toothbrushes assert that the activated charcoal particles in the bristles can help eliminate toxins and reduce bacterial growth in the mouth, potentially promoting fresher breath and improved gum health. Conclusion: The results of this study concluded the abrasive nature of charcoal may increase surface roughness of teeth after prolonged use.,